KINERJA KEUANGAN DALAM PERSPEKTIF LINGKUNGAN: STUDI PADA PERUSAHAAN MANUFAKTUR INDONESIA - Machfudt, Yusuf; BZ, Fazli Syam (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
This study purposes to determine the effect of Environmental Costs, Environmental Performance, and Corporate Social Responsibility (CSR) on Financial Performance. The type of data used is quantitative data. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period, totaling 193 companies with a sample of 8, obtained by the purposive sampling method. The analytical method used is Multiple Linear Regression Analysis. The results of this study are that environmental costs have a negative effect on financial performance, environmental performance has no effect on financial performance, and corporate social responsibility has no effect on financial performance.